Case report: Ultrasonographic and computed tomographic imaging features of hemochromatosis in a dog - Choi, Mihyun; Lee, Namsoon (Frontiers in Veterinary Science, 2024)
A castrated male mixed-breed dog weighing 7kg presented with elevated liver enzymes and anorexia. Abdominal radiography revealed hepatomegaly with heterogeneous hepatic opacification and abdominal ultrasonography showed a fine echotexture, and heterogeneous parenchyma concurrent with a suspected acquired portosystemic shunt. Pre-contrast computed tomography (CT) showed marked hepatomegaly with homogeneous increased liver density and multiple enlarged abdominal lymph nodes with markedly increased parenchymal density. Histopathology of the hepatic and lymph node biopsy revealed accumulated abundant hemosiderin, and Prussian Blue stain confirmed marked iron accumulation within the hepatocytes. Based on our review of the literature, this is the first case report describing the imaging diagnosis of hemochromatosis in a dog.